Topographical Characteristics of Frequent Inland Water Flooding Areas in Tangerang City, Indonesia - Djamres, Eilif Kurnia Deda; Komori, Daisuke; Kazama, So (Frontiers in Water, 2021)
The methodology examined for this study was based on statistical analyses and GIS computations of frequent inland water flooding areas in Tangerang city, Indonesia during 2008–2015. Primary data used for this study were inland water flooding records from Tangerang city government and an approximately 90 m Merit DEM. We extracted the topographical characteristics of frequent inland water flooding areas and used principal component analysis to find its main characteristics. Results show that frequent inland water flooding areas in Tangerang emerged because of a slope in the upstream condition, the correlation between concave and flow length conditions, correlation of the slope condition and distance to a river, and relations among flow length in upstream characteristics and distance to a pond. Furthermore, a principal component score of frequent inland water flooding areas and other areas in the city was compared with measure similarity. This method correctly identified 71% of frequent inland water flooding areas. Also, 74% of one-time inland water flooding areas were classified as locations with high topographical similarity. Furthermore, field surveys indicated that the remaining 29% of frequent inland water flooding areas had low topographical similarity because of anthropogenic factors.